Touch Screen Device Swipe n Share - Khokale, Praful; Gunjal, Narendra; Suhas B, Gote (International Journal of Computer Sciences and Engineering, 2025)
There are communication commonly extend across smart-phones and devices with wider screens. Indeed, data might be received on the Smart devices but more conveniently processed with an application on a smart device, or vice versa. Such communication require automatic data sharing from a sending location on one screen to a receiving location on the other device screen. We bring out a touch screen device Swipe n Share technique to facilitate these communication involving multiple touchscreen devices, with minimal effort for the user. The technique is a two-handed device gesture, where one hand is used to suitably align the mobile phone with the larger screen, while the other is used to select and swipe an object between devices and choose which device receive the data.